Socioeconomic Status Modifies the 20-Year Association Between Metabolic Syndrome and Incident Coronary Artery Disease: A Nationwide Cohort Study of Korean Adults - U Chul Ju; Ja Young Kim; Hyun Yi Kook; Yeon Ji Seong; Ho Goon Kim; Eujene Jung (Journal of Clinical Medicine, 2026)
Background/Objectives: Metabolic syndrome (MetS) and low socioeconomic status (SES) are each established drivers of coronary artery disease (CAD), a leading cause of acute cardiovascular presentations to emergency and acute care services. Whether SES modifies the long-term association between MetS and CAD in a universal health coverage setting is unclear. We examined the independent and joint associations of MetS and income-based SES with 20-year incident CAD. Methods: In this nationwide retrospective cohort study using the Korean National Health Insurance Service database, 489,521 adults aged 40–79 years who underwent a national health examination in 2005 and were free of CAD at baseline were followed through 31 December 2024 (up to 20 years). At baseline, the mean age was 54.1 ± 9.2 years, and 252,818 participants (51.6%) were men. MetS was defined by modified harmonized criteria, with body mass index (BMI) ≥ 25 kg/m2 substituted for waist circumference. SES was measured by health insurance premium deciles and classified as high (deciles 8–10), middle (4–7), low income (1–3), and Medical Aid (decile 0). The outcome was incident CAD (myocardial infarction or angina pectoris). Multivariable Cox proportional hazards models were adjusted for age, sex, smoking, alcohol consumption, regular exercise, BMI, chronic kidney disease, alternate exposure, and estimated adjusted hazard ratios (aHRs); joint exposure and additive interaction (relative excess risk due to interaction, RERI) were assessed. Results: MetS prevalence was 30.6%. During follow-up, 48,428 participants (9.9%) developed CAD. MetS was independently associated with CAD (aHR 1.84; 95% CI 1.78–1.91), as was a graded socioeconomic gradient (Medical Aid vs. high SES aHR 1.62; 1.54–1.70). Incidence rates ranged from 3.13 (high-SES without MetS) to 11.40 (Medical Aid with MetS) per 1000 person-years. In the joint analysis, Medical Aid beneficiaries with MetS had the highest risk (aHR 2.92; 2.78–3.08 vs. high-SES without MetS; p for interaction < 0.001), with positive additive interaction (RERI 0.68). Conclusions: Over two decades, low SES amplified the CAD burden associated with MetS. Adults living in the most severe material deprivation who also had MetS constituted the highest risk group, of direct relevance to risk stratification and disparities in emergency and acute cardiovascular care.